Degradation of metaldehyde in aqueous solution by nano-sized photocatalysts and granular activated carbon - Kim, Jong Kyu; Jiang, Tingting; Li, Zhoujun; Mayadevi, Suseeladevi; Bharat, Kale; Joo, Jin Chul; Campos, Luiza Cintra (Journal of Nanoscience and Nanotechnology, 2020)
Metaldehyde has been detected in drinking water system in relatively high concentration exceeding European water quality standard. In order to address this problem, the aim of this project was to treat metaldehyde aqueous solution by advanced oxidation processes (AOPs) and granular activated carbon (GAC) column. Ten novel materials were tested for degradation rates of metaldehyde under ultraviolet light irradiation (UVC). For treatment of 1 mg/L metaldehyde solution by AOPs, the highest degradation rate is 16.59% under UVC light with the aid of nitrogen doped titanium dioxide coated graphene (NTiO2/Gr). Furthermore, 0.5 mg/L is the optimal concentration for degradation of metaldehyde with N-TiO2/Gr under UVC light. Apart from that, the lifetime of GAC column could be elongated on condition that metaldehyde has been treated by AOPs previously. Hence, combination of AOPs and GAC column is promising in treating water containing metaldehyde.